2009
DOI: 10.3233/bmr-2009-0237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body weight supported treadmill training on cardiac and pulmonary functions in the patients with incomplete spinal cord injury

Abstract: We aimed to investigate the effects of body weight supported treadmill training (BWSTT) on cardio-pulmonary functions and on depression in subjects with incomplete spinal cord injury (SCI). Eight subjects (2 female, 6 male) with incomplete SCI participated in this study. Heart rate (HR), blood pressure (BP) and resting pulmonary function parameters were obtained from each subject at baseline and after BWSTT. The training programme was scheduled five times per week for six weeks. The psychological status was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 18 publications
1
28
1
Order By: Relevance
“…Most studies investigating robot-assisted gait training in iSCI focused on the effectiveness of improving neurologic and motor function and concluded that it is an appropriate therapy for improving walking ability [16][17]. Although there is some knowledge with regard to the cardiovascular effects of BWS treadmill training with manual assistance [13,[18][19][20][21], little is documented about the cardiorespiratory effects of robot-assisted gait training.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigating robot-assisted gait training in iSCI focused on the effectiveness of improving neurologic and motor function and concluded that it is an appropriate therapy for improving walking ability [16][17]. Although there is some knowledge with regard to the cardiovascular effects of BWS treadmill training with manual assistance [13,[18][19][20][21], little is documented about the cardiorespiratory effects of robot-assisted gait training.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of LT on pulmonary function have been mentioned previously in the literature. [5][6][7] Soyupek et al 5 investigated the heart rate, blood pressure, resting pulmonary function parameters and psychological status (using the Beck Depression Inventory) of eight subjects (two females and six males) with incomplete SCI at baseline and after BWSTT. They found that undergoing BWSTT for 6 weeks had a positive effect on heart rate and limited effect on pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies have focused on the effects of LT on the functional walking ability of patients with SCI, it also has many positive effects as a whole-body exercise procedure, such as on cardiopulmonary function, body composition and quality of life. 4,5 Until recently, however, the effects of LT on the respiratory system have received little attention. Soyupek et al 5 investigated the heart rate, blood pressure and resting pulmonary function parameters at baseline and after BWSTT of eight subjects (two female, six male) with incomplete SCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of spinal cord injury patients have addressed functional improvements achieved through pulmonary rehabilitation, such as electrical stimulation and exercise [8][9][10] , but relatively few studies have examined the effect of position on pulmonary measurements of spinal cord injury patients. In the present study, we studied whether position affects measured lung capacity of spinal cord injury patients.…”
Section: Introductionmentioning
confidence: 99%